Product of binomial coefficients

Algebra Level 3

If P n P_{n} denotes the product of all the binomial coefficients in the expansion of ( 1 + x ) n (1+x)^n , then P n + 1 P n \frac{P_{n+1}}{P_{n}} equals

Clarification : Binomial Coefficients are ( n r ) {n \choose r} OR n C r ^{n}C_{r}

( n + 1 ) n + 1 ( n + 1 ) ! \frac{(n+1)^{n+1}}{(n+1)!} ( n + 1 ) n ! \frac{(n+1)}{n!} n n n ! \frac{n^{n}}{n!} ( n + 1 ) n ( n + 1 ) ! \frac{(n+1)^{n}}{(n+1)!} n n ( n + 1 ) ! \frac{n^{n}}{(n+1)!}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Ravi Dwivedi
Oct 21, 2015

P n = n C 0 n C 1 n C 2 n C n P_{n}= ^{n}C_{0} \cdot ^{n}C_{1} \cdot ^{n}C_{2} \cdot \cdot \cdot ^{n}C_{n}

P n + 1 = n + 1 C 0 n + 1 C 1 n + 1 C 2 n + 1 C n + 1 P_{n+1}= ^{n+1}C_{0} \cdot ^{n+1}C_{1} \cdot ^{n+1}C_{2} \cdot \cdot \cdot ^{n+1}C_{n+1}

Now P n + 1 P n = n C 0 n C 1 n C 2 n C n n + 1 C 0 n + 1 C 1 n + 1 C 2 n + 1 C n + 1 \frac{P_{n+1}}{P_{n}} = \frac{^{n}C_{0} \cdot ^{n}C_{1} \cdot ^{n}C_{2} \cdot \cdot \cdot ^{n}C_{n}}{^{n+1}C_{0} \cdot ^{n+1}C_{1} \cdot ^{n+1}C_{2} \cdot \cdot \cdot ^{n+1}C_{n+1}}

P n + 1 P n = ( n + 1 C 1 n C 0 ) ( n + 1 C 2 n C 1 ) ( n + 1 C 3 n C 2 ) ( n + 1 C n + 1 n C n ) \implies \frac{P_{n+1}}{P_{n}} =( \frac{^{n+1}C_{1}}{^{n}C_{0}})( \frac{^{n+1}C_{2}}{^{n}C_{1}})( \frac{^{n+1}C_{3}}{^{n}C_{2}}) \cdot \cdot \cdot ( \frac{^{n+1}C_{n+1}}{^{n}C_{n}})

P n + 1 P n = ( n + 1 1 n C 0 n C 0 ) ( n + 1 2 n C 1 n C 1 ) ( n + 1 3 n C 2 n C 2 ) ( n + 1 n + 1 n C n n C n ) \implies \frac{P_{n+1}}{P_{n}} =( \frac{\frac{n+1}{1} \cdot^{n}C_{0}}{^{n}C_{0}})( \frac{\frac{n+1}{2} \cdot^{n}C_{1}}{^{n}C_{1}})( \frac{\frac{n+1}{3}\cdot ^{n}C_{2}}{^{n}C_{2}}) \cdot \cdot \cdot ( \frac{\frac{n+1}{n+1}\cdot^{n}C_{n}}{^{n}C_{n}})

P n + 1 P n = ( n + 1 1 ) ( n + 1 2 ) ( n + 1 3 ) ( n + 1 n + 1 ) = ( n + 1 ) n + 1 ( n + 1 ) ! \implies \frac{P_{n+1}}{P_{n}} = (\frac{n+1}{1})(\frac{n+1}{2})(\frac{n+1}{3})\cdot \cdot \cdot (\frac{n+1}{n+1})= \boxed{\frac{(n+1)^{n+1}}{(n+1)!}}

Moderator note:

Good usage of ( n + 1 k + 1 ) = n + 1 k + 1 × ( n k ) { n+1 \choose k + 1 } = \frac{n+1}{k+1} \times { n \choose k } .

The first step need correction

Ahmed Nabih - 2 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...